2016
DOI: 10.24289/ijsser.279006
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the level of mindfulness and entrepreneurship of the university students

Abstract: The aim of this study is to analyze mindfulness and entrepreneurial orientation of university students. The sample of the study involves 534 people in total, 364 of them are males and 170 are females, who studied in Bartın University, School of Physical Education and Sports in 2015-2016 academic year. "Mindfulness Attention Awareness Scale", which has been developed by Brown and Ryan (2003) and adopted into Turkish by Özyeşil et al. (2011) and "Entrepreneurship Scale for University Students" developed by Yı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…There are many studies in the literature on mindful attention awareness (Celik, & Cetin, 2014;Cengiz, Serdar & Donuk, 2016;Gulum, 2017;Saricali & Satici, 2017;Kara & Ceyhan, 2017;Deniz, Erus & Buyukcebeci, 2017;Meiklejonh et al, 2012;Schonert-Reichl & Lawlor, 2010;Sample, 2010) and ruminative thought styles (Graham et al, 2018;Gustavson et al, 2018;Robinson & Alloy, 2003;Topcu, 2014;Cilali, 2015;Onayli, 2019;Aksoz-Efe, 2018). When the information above is evaluated as a whole, it is observed that the concepts of mindful attention awareness and ruminative thought can be effective in different areas of life to various extents.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies in the literature on mindful attention awareness (Celik, & Cetin, 2014;Cengiz, Serdar & Donuk, 2016;Gulum, 2017;Saricali & Satici, 2017;Kara & Ceyhan, 2017;Deniz, Erus & Buyukcebeci, 2017;Meiklejonh et al, 2012;Schonert-Reichl & Lawlor, 2010;Sample, 2010) and ruminative thought styles (Graham et al, 2018;Gustavson et al, 2018;Robinson & Alloy, 2003;Topcu, 2014;Cilali, 2015;Onayli, 2019;Aksoz-Efe, 2018). When the information above is evaluated as a whole, it is observed that the concepts of mindful attention awareness and ruminative thought can be effective in different areas of life to various extents.…”
Section: Introductionmentioning
confidence: 99%